Litho- and biostratigraphy, facies patterns and depositional sequences of the Cenomanian-Turonian deposits in the Ksour Mountains (Saharan Atlas, Algeria) - Benyoucef, Madani; Ifrim, Christina (Cretaceous research, 2017)
The Cenomanian-Turonian deposits exposed in the Ksour Mountains, western part of the Saharan Atlas (Algeria), document marine shelf environments that had been thriving on the North African passive margin, connected northwards to the Tethys Ocean, and fringed southwards by the Saharan craton. Their lithological, palaeontological, and sedimentological characteristics have been investigated to provide new insights into the biostratigraphy, palaeo-environmental evolution and sea-level changes in this western part of the Saharan Atlas. Three formations are recognized, from base to top of the studied succession: 1. The El Rhelida Formation comprising two informal units: the mixed siliciclastic-carbonate unit deposited under different flow regime conditions, from shoreline to backshore environments, and the limestone-claystone unit including coastal mudflat deposits prone to storm events. The early Cenomanian age of the El Rhelida Formation is supported by vertebrate assemblages. 2. The Mdaouer Formation comprising two units: the evaporitic unit dominated by claystone and evaporite alternations deposited on a flat coastal sabkha with occasional storms, and the marlstone-limestone unit formed in a peritidal-lagoonal environment. The Mdaouer Formation is of early-middle Cenomanian age. 3. The Rhoundjaïa Formation comprising three units: the lower limestone unit consisting of relatively homogeneous fossiliferous limestones; the middle marly unit composed of marlstone and bioclastic limestones, and the upper limestone unit consisting of carbonates showing vertical variations in faunal content and stratonomy. The Rhoundjaïa Formation was deposited in homoclinal ramp setting. Ammonite data indicate an early late Cenomanian to early Turonian age for this interval. Within an overall transgressive trend, the Cenomanian-Turonian deposits of the Ksour Mountains record three third-order depositional sequences bounded each by regional discontinuities.
Gesehen am 13.04.2018
DOI funktioniert nicht